Effect of storage period on trichocards parasitized by Trichogramma chilonis Ishii under laboratory conditions: Storage period of Trichogramma - Ajudia, Dhruvi; Siddhapara, MR (ORYZA-An International Journal of Rice, 2024)
The present study aimed to find the suitable storage duration for parasitized trichocards without affecting much the biological parameters of T. chilonis adults such as adult emergence, adult longevity and egg parasitization. The results revealed that biological parameters viz., adult emergence, adult longevity and egg parasitization were inversely proportional to the storage period. Maximum adult emergence (87.63%), female longevity (5.57 days), male longevity (4.53 days) and egg parasitization (85.67%) were observed at 5 days storage period. Further, adult emergence declines to 56.13 per cent when trichocards are stored for 25 days. Whereas, less than 50 per cent egg parasitization in F1 generation was observed when trichocards were stored for 35 days. However, there was no egg parasitization by a female in the F1 generation noticed for 45 and 50 days storage period this might be due to short adult female longevity and lowest adult emergence. Hence, it can be concluded that trichocard could be effectively stored for up to 25 days at low temperatures under refrigerator conditions(4°C temperature and 50-60% relative humidity) by considering at least 50 per cent adult emergence with 4.13 days of female longevity as well as 63.00 per cent egg parasitization during the mass production program. Therefore, effective and right time augmentation of T. chilonis could be achieved under field conditions.